O impacto do gênero fanfiction no letramento digital - Alves, Myrna Andreza da Silva (2023)
With technological development, human beings change, build and rebuild the forms of interaction between their peers around the world. In this scenario, writing and reading, little by little, also adapt to the new times, like the productions of fans – known as fanfictions. Made available on the internet, creating fans can generate, therefore, a mass network of readers and content creators – as occurred with the productions incorporated in the Harry Potter saga. Throughout the development of the study, he suffered that there are, in this universe of research, many more questions than answers; which may be interesting, as, in our view, it makes clear the innovative character of a topic that is increasingly updated. In this way, the problem aims to question how the fanfiction genre can impact digital literacy. Therefore, the general objective is limited to analyzing the influences of fan productions on digital literacy, seeking to highlight factors such as inclusion, popularization, among others. Therefore, the methodological approach is done through a bibliographical research. In addition to materials in books, articles and magazines, it was also necessary to visit websites and blogs; as well as a searchable object selection process and content reviews. Therefore, the study is organized into three chapters: in the first, there is a contextualization about the evolution and evolution of fanfic; the second takes place through an investigation into digital literacy and its specificities and the third chapter is left to the most popular platforms and fics, as well as the importance of fan production in the culture of digital literacy. Finally, for the elaboration, problematization and reflection of the questions listed here, we resort to theoretical contributions from the technological, literary and related areas, such as LÉVY (2000), CANDIDO (2006), CHARTIER (2002), JAMISON (2017), MEDEIROS (2019), among others. In this perspective, we believe that the contribution of this research to the area of letters and the like is, among other factors, in the attempt to understand the phenomenon that has become this type of fan production and the mass consumption of this content by the readers; as well as to reflect on the place of fanfic in the literary role, and, therefore, in promoting reading, without forgetting the initial contribution that our study can provide for new research.